2012
DOI: 10.1371/journal.pone.0049272
|View full text |Cite
|
Sign up to set email alerts
|

Change in Brain Magnetic Resonance Spectroscopy after Treatment during Acute HIV Infection

Abstract: ObjectiveSingle voxel proton magnetic resonance spectroscopy (MRS) can be used to monitor changes in brain inflammation and neuronal integrity associated with HIV infection and its treatments. We used MRS to measure brain changes during the first weeks following HIV infection and in response to antiretroviral therapy (ART).MethodsBrain metabolite levels of N-acetyl aspartate (NAA), choline (tCHO), creatine (CR), myoinositol (MI), and glutamate and glutamine (GLX) were measured in acute HIV subjects (n = 31) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 28 publications
8
84
0
Order By: Relevance
“…A recent acute infection study has identified elevations of Cho/Cr in the basal ganglia at 14 days postexposure and its subsequent reduction to control levels with 6 months of ART. 29 The reduction of basal ganglia Cho/Cr in that study may be related to the earlier initiation of ART than in our study. It is also possible that this is a region-specific observation, as the study also noted a Cho/Cr elevation in the occipital gray matter at baseline that was not reduced upon ART initiation.…”
Section: Magnetic Resonance Spectroscopysupporting
confidence: 37%
See 2 more Smart Citations
“…A recent acute infection study has identified elevations of Cho/Cr in the basal ganglia at 14 days postexposure and its subsequent reduction to control levels with 6 months of ART. 29 The reduction of basal ganglia Cho/Cr in that study may be related to the earlier initiation of ART than in our study. It is also possible that this is a region-specific observation, as the study also noted a Cho/Cr elevation in the occipital gray matter at baseline that was not reduced upon ART initiation.…”
Section: Magnetic Resonance Spectroscopysupporting
confidence: 37%
“…All individuals reported symptoms of acute HIV syndrome and 5 additionally reported severe headaches, numbness in extremities, and difficulty thinking clearly. 30 In predominantly less symptomatic acute infection studies, no significant differences in baseline NAA/Cr were identified, 10,29 though this may be limited by sample size. Similarly, we report no significant differences in baseline NAA/Cr in PHI as compared to HIV-uninfected controls, but low NAA/Cr in parietal gray matter trended toward significance (p 5 0.064).…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 2 Adjusted relative risk for symptomatic progression: Asymptomatic neurocognitive impairment vs neurocognitively normal addition, neuroimaging studies find detectable structural, functional, and spectroscopic evidence of brain abnormalities even in the acute and early phases of HIV infection. [21][22][23][24][25] Of interest, those with ANI at baseline had evidence of more advanced prior HIV disease, e.g., lower nadir CD4 and greater likelihood of an AIDS diagnosis. This finding supports the concept that ANI is an HIV-driven process that, like more severe forms of HAND, is more likely with greater levels of prior immunosuppression.…”
mentioning
confidence: 99%
“…Furthermore, markers of immune activation may reflect the degree of viral load and neurocognitive impairment [16]. Magnetic resonance spectroscopy (MRS), a noninvasive quantitative MR technique that measures alterations in cerebral metabolite levels, demonstrates that inflammatory cerebral metabolites are elevated in acute HIV infection (ie, the period before antibody seroconversion) and longitudinally increased over time in PHI before cART initiation [1,17,18]. Thus, crucial processes during the primary phase of viral infection may underlie the initiation of HIV-associated CNS injury.…”
mentioning
confidence: 99%